Stability of partial and complete resistance in rice to Pyricularia grisea under rainfed upland conditions in Eastern Colombia - Correa Victoria, Fernando J.; Zeigler, Robert S. (Scientific Societies, 1995)
Two sets of experiments were conducted to compare the relative stability of partial and complete resistance in rice to Pyricularia grisea (causal agent of the rice blast disease) in a disease hot spot in eastern Colombia. In the first set of experiments, 186 breeding lines selected at the site over the F2 to F4 generations, ranging from completely to partially resistant in the F4, were evaluated under heavy disease pressure at the site every season from 1987 to 1990 (two seasons per year). A set of 92 lines from the International Rice Blast Nursery (IRBN) with initial evaluations of resistant (standard evaluation system [SES] ? 5), also ranging from completely to partially resistant, were evaluated under the same conditions. Locally developed materials were rated as susceptible less frequently than lines from the IRBN set. In both sets, significantly fewer lines initially scored as highly resistant (SES = 1 to 3) were later scored as susceptible (SES > 5) or showed any increase in susceptibility to local pathogen populations compared to those initially rated as partially resistant (SES = 4 to 5). In the second set of experiments, locally developed and exotic lines were grouped according to partial (few susceptible-type lesions [SES type 5]) and high resistance (few resistant-type lesions [SES type 1 to 3]). After three seasons of evaluation, lines with high levels of resistance had a significantly lower rate of change to susceptible levels. The rice cultivar Oryzica Llanos 5 was selected at this site from a line with complete blast resistance and was released for commercial cultivation in blast-prone eastern Colombia. It is grown on approximately 5 × 104 ha/year and has remained resistant to blast over 10 consecutive growing seasons, both in experimental blast nurseries and in farmers fields where blast normally is a severe problem. This cultivar also showed uniformly high levels of blast resistance when evaluated at seven high blast level sites in four Asian countries in blast nurseries with 72 other cultivars with differing levels and origins of blast resistance. The results suggest that selecting high levels of resistance when diverse sources are combined can be used to develop cultivars with stable resistance to rice blast.